A radiação é vilã? possibilidades de alfabetização científica na educação básica - Bárbara Maxilene Lucas Lima (2023)
This study was developed in the Master's Degree Program in Education and Teaching (PROMESTRE) at FaE/UFMG in the Science Teaching area. In science teaching, the approaches of inquiry teaching and Science, Technology and Society (STS) have been gaining strength and supporters to promote scientific literacy. These approaches use resources and strategies to motivate students to perceive meaning in themes in order to approximate the theory to the society. Aiming to promote scientific literacy and lead students to question themselves about the types of radiation, its effects and its applications in society associated with technologies involving radiation and radioactivity, this study presents the design, validation, development and analysis of an investigative teaching sequence (ITS) based on radiation and radioactivity. The choice of this theme was made because, although unknown to many, radiation plays a fundamental role in some areas, but unfortunately it is through its risks that it is disseminated by the media. The sequence was prepared and presented to tutors from a specialization course and to undergraduate students in the last period of the undergraduate Chemistry course, who contributed to the organization and suggestions for substitution of activities. The sequence was re-designed and applied to an 8th grade class of Elementary II of a private school in the city of Contagem. During the ITS application, audios were recorded for later data analysis using Textual Discourse Analysis (TDA). We considered as a priori categories indicators of scientific literacy presented in the literature that are similar to scientific practices as well as indicators presented in more recent studies based on the previous ones that seek to bring the scientific practice closer to the classroom. During the analysis of the audios, the TDA allowed four other categories to emerge, which are called emerging categories: quantification - the students tried to compare the different consequences of exposure to radiation; impacts - they related exposure to radiation to the impacts caused by this exposure; applications - when asked how radiation is present in society, they classified it into three areas of application; types of radiation - it was observed that the students tried to classify radiation into four types, which they called good, bad, weak and strong. Based on the categorization provided by the TDA, it was possible to identify, in the students' speeches, several moments in which the promotion of scientific literacy occurred. The results were presented using the self-organized process of construction of understanding of the TDA, called metatexts.